Estrategias para fortalecer el vínculo docente-alumno y mejorar el aprendizaje significativo - Novillo Bonifaz, Nataly Gabriela (2024)
The primary objective of this research was to propose strategies to strengthen the teacher-student bond to enhance meaningful learning within the educational environment. To achieve this, it is crucial to elucidate the teacher-student relationship within the classroom, analyze the bond, and determine the pedagogical practices that educators apply to achieve meaningful learning among students. Methodologically, this study employed a qualitative approach with a phenomenological design, identifying, analyzing, and determining the experiences, strategies, and lived realities of teachers and students within the classroom. The phenomenon was described and understood from the participants' perspectives, supported by a bibliographic and documentary review to gather data about the institution's population. Techniques utilized included observation and interviews, employing an observation sheet and a semi-structured interview guide as instruments. The selected sample was intentional, non-probabilistic, comprising 2 teachers and 81 students. Analytical methods were used to analyze the findings, based on the theoretical framework, observations, and interview responses. The interviewed teachers expressed a strong interest in learning new strategies to support their students' development. Although noticeable differences in classroom behavior were observed between the teachers, both demonstrated effectiveness in imparting knowledge and enabled students to take an active role in their learning construction. It was concluded that integrating content and emotions in the classroom is necessary to facilitate effective teacher-student interaction. Recommendations include using didactic resources and techniques for meditation and self-awareness to help students self-regulate and stay motivated. Finally, specific strategies have been proposed to strengthen the teacher-student bond and improve meaningful learning